Модель та інформаційна технологія побудови адаптивної матриці трасування вимог у гнучких процесах розробки програмного забезпечення - Тамзаєв, Р. О.; Ткачук, Микола Вячеславович (НТУ "ХПІ", 2013)
Some features of requirements management in agile software development are considered, and problem actuality to elaborate respective requirements traceability tools for their effective implementation is defined. An approach is proposed, which is based on an algorithm-centered model to build adaptive traceability matrix and on usage of information technology to collect and to process data related to requirements, project artifacts and project's stakeholders participated in iterative software development.
Keywords: розробка адаптивна; функція ступеню інтересу; модель алгоритмічна; накопичення даних; опрацювання даних; артефакти проектні; процес ітераційний